A descriptive Analysis of Anglicisms used in Ecuadorian Magazines. - Pinto Andrade, Ramona Del Pilar (2011)
The theme for this research is “A DESCRIPTIVE ANALYSIS OF ANGLICISMS IN ECUADORIAN MAGAZINES”. The investigation took place in Quito - Ecuador, and was done based on the analysis of three variables: Cultural, Scholarly and General Interest Magazines. The samples were taken from the following Ecuadorian magazines: Vistazo, Estadio, PC World Ecuador, Gestion, La Casa and Letras de Ecuador.